(untitled) (European Science Methodical Journal, 2026)
Entamoeba histolytica is a common parasite worldwide, particularly in Iraq. This statistical study adds new findings confirming human infection with this parasite and its role in causing gastrointestinal disorders. The study was conducted in Kirkuk, Hawija District, at the Hawija General Hospital laboratory, on 120 samples randomly collected between February 2024 and February 2026. Direct examination of stool samples revealed that the cause of diarrhea was Entamoeba histolytica infection. Microscopic examination using wet swabs and flotation/sedimentation methods was performed to detect larval and cystic stages. The study also revealed the infection rates between males and females, with males showing a higher rate of 65%. The highest infection rates were recorded in November (40%) and June (14%). The most affected age group was children aged 1 to 10 years (45%), followed by adolescents aged 11 years and older (20.8%).